Functional capacity and quality of life improvement in stable chronic obstructive pulmonary disease (COPD) patients following physical exercise and chicken egg white supplementation - Sihombing, Benny; Tarigan, Amira P.; Pandia, Pandiaman; Zaluchu, Fotarisman; Sinaga, Bintang YM.; Monica, Nanda S.; Rhinsilva, Ella; Zulkarnain, Zulkarnain (Narra Sains Indonesia, 2023)
The pillars of comprehensive pulmonary rehabilitation program for chronic obstructive pulmonary disease (COPD) patients include physical exercise and good nutrition. The aim of this study was to evaluate the efficacy of pulmonary rehabilitation, which included physical exercise and chicken egg white supplementation, on the quality of life (QoL) and functional capacity among patients with stable COPD. The COPD patients were enrolled prospectively in this quasi-experimental study and completed a 12-week smartphone-guided home-based physical exercise program that comprised strength and resistance training three times per week for 30 minutes each session. Participants were divided into two groups: the control group who underwent physical exercise only, and the intervention group who had physical exercise and chicken egg white supplementation as a protein source. Patient characteristics including sex, age, nutritional status, comorbidities, smoking status, and obstruction severity, were evaluated. The COPD assessment test (CAT) score and six-minute walk test (6MWT) were used as the parameters to evaluate QoL and functional capacity, respectively. Of the total 50 patients included in the study, 12 were excluded due to follow-up and adherence problems. Our data indicated there were significant CAT score reduction and 6MWT improvement in both control and intervention groups after 12 weeks compared to baseline data. However, reduction of mean CAT score was higher in intervention compared to control group (-13.47±6.49 vs -5.42±5.07, p<0.001). In addition, the improvement of 6MWT was also higher in intervention group compared to control group (145.47±69.2 vs 32.42±17.3 meters, p<0.001). In conclusion, chicken egg white supplement to male patients with stable COPD who exercise with resistance and strength training could improve the QoL and functional capacity.